COLLABORATIVE GOVERNANCE ANTARA BAPPEDA PROVINSI JAWA TIMUR DAN PT SARANA TIRTA ABADI DALAM PENGELOLAAN OUTSOURCING - Saifullah Fatah Wardana, Laskar Intifada; Kistyanto, Anang; Megawati, Suci (Penerbit Lafadz Jaya, 2025)
This study seeks to identify and evaluate the practice of collaborative governance within the public–private partnership between the East Java Provincial Development Planning Agency (BAPPEDA) and PT Sarana Tirta Abadi in the management of outsourced personnel. Employing a qualitative approach that integrates in-depth interviews, field observations, and analysis of contractual and administrative documents, this research examines the dynamics of collaboration using the four dimensions of the Ansell and Gash model: starting conditions, institutional design, collaborative process, and facilitative leadership. The findings indicate that interactions between the actors remain framed by hierarchical authority structures, thereby limiting the private partner’s participation in policy formulation, performance monitoring, and operational strategy development. Power imbalances, non-deliberative institutional arrangements, and weak collaborative communication further hinder the formation of effective joint action. Based on these results, the study recommends the development of shared operational guidelines—including Joint Performance Indicators and a Service Level Agreement—the establishment of inclusive and periodic evaluation forums, and the strengthening of facilitative leadership as essential elements for fostering a more equitable, adaptive, and sustainable model of collaborative governance in managing outsourced personnel within regional government institutions.